Tumor organoids in immunotherapy: from disease modeling to translational research - Jing Ma; Jianping Song; Zhuolong Zhou; Qi Si; Shuhan Tao; Jizhun Wu; Zhengxing Li; Xiaohang Feng; Tiantian Kong (Journal for ImmunoTherapy of Cancer, 2025)
Tumor organoids have emerged as transformative tools in cancer research, enabling the study of tumor biology and immunology in a physiologically relevant, three-dimensional in vitro environment. Derived from patient tumor samples, these self-organizing structures recapitulate the histological and genetic heterogeneity of tumors and their microenvironment, offering significant advantages over traditional two-dimensional cell cultures and animal models. This work provides a comprehensive overview of tumor organoid generation, their characteristics, and their use as models to study tumor-immune interactions. We discuss how tumor organoids faithfully recapitulate tumor heterogeneity, support immune cell infiltration, and simulate immunosuppressive environments, making them ideal platforms for investigating immunotherapy strategies. Emerging technologies, including advanced imaging and single-cell analysis, as well as gene editing tools, further enhance the utility of tumor organoids in dissecting immune-tumor interactions at unprecedented resolution. We also highlight the translational potential of tumor organoids in preclinical immunotherapy research. Organoids offer a promising approach for predicting patient response to immunotherapy and developing personalized treatment strategies. As tumor organoid technology continues to evolve, its application in clinical settings holds great promise for advancing cancer immunotherapy, improving patient outcomes, and overcoming the challenges of drug resistance. Finally, the future direction of tumor organoid development is speculated according to current challenges.